Analyzing the impact of exchange rate fluctuations and inflation on the GDP in Iraq using the modern methodology of Cointegration for the period (1988-2020) - Al-Bayati, Dalia Omar Nazmi; Al-Dulaimi, Saif Adel Sabbar; Al-Mihimdy, Nadhem Abdullah Abid (Journal of Economics and Administrative Sciences, 2022)
The research aims to analyze the impact of exchange rate fluctuations (EXM and EXN) and inflation (INF) on the gross domestic product (GDP) in Iraq for the period 1988-2020. The research is important by analyzing the magnitude of the macroeconomic and especially GDP effects of these variables, as well as the economic effects of exchange rates on economic activity. The results of the standard analysis using the ARDL model showed a long-term equilibrium relationship, according to the Bound Test methodology, from explanatory (independent) variables to the internal (dependent) variable, while the value of the error correction vector factor was negative and moral at a level less than (1%). The relationship between EXM and GDP was inverse, with partial flexibility for EXM (-7.666), meaning that an increase in EXM (1%) will lead to a decrease in GDP (7.666%). This applies to the reality of the Iraqi economy, as the method used in recent times is to devalue the local currency. The effect of EXN was steady in the long run, with the partial flexibility of EXN (5.785), that is, an increase of EXN (1%) will lead to an increase in GDP (5.785%), and the model as a whole is statistically significant. The explanatory power of the model is high, as it was (R2=0.816), indicating that 81% of the changes in GDP in constant prices are due to the change in (EXM, EXN, and INF). The study concluded that in light of the outbreak of the coronavirus, the disruption of most economic projects, and the decline in the prices of the Iraqi government, as a result of the decrease in the balance of oil and oil revenues, as a result of the balance of the government part of the solution is to devalue the local currency by controlling the nominal exchange rate. At present, the Iraqi Monetary Authority recommends that the Managed Flexible Exchange System be continued as an effective means of avoiding external shocks for the Iraqi economy, as it allows for appropriate adjustments to be made continuously